There’s just huge anxiety: ontological security, moral panic, and the decline in young people’s mental health and well-being in the UK - Jo Bell; Marie Reid; Judith Dyson; Annette Schlosser; Tim Alexander (Qualitative Research in Medicine & Healthcare)
This study aims to critically discuss factors associated with a recent dramatic rise in recorded mental health issues amongst UK youth. It draws from interviews and focus groups undertaken with young people, parents and professionals. We offer valuable new insights into significant issues affecting young people’s mental health and well-being that are grounded in their lived experiences and in those who care for and work with them. By means of a thematic analysis of the data, we identified an increase in anxiety related to: future orientation, social media use, education, austerity, and normalization of mental distress and self-harm. We apply the notion of ontological security in our interpretation of how socio-cultural and political changes have increased anxiety amongst young people and consequent uncertainty about the self, the world and the future, leading to mental health problems. There are also problems conceptualizing and managing adolescent mental health, including increased awareness, increased acceptance of these problems, and stigmatisation. We relate this to the tendency for moral panic and widespread dissemination of problems in a risk society. In our conclusion, we highlight implications for future research, policy and practice.